DISTRIBUTION AND COENOFLORA OF DAPHNE ALTAICA (THYMELAEACEAE) – A RARE ENDEMIC SPECIES FROM EASTERN KAZAKHSTAN (Experimental biology, 2022)
Daphne altaica is a rare endemic species from East Kazakhstan, which is of great scientific interest. As a result of the study, data were obtained on the distribution and coenoflora of the rare endemic species Daphne altaica in East Kazakhstan. The concentration of habitats falls on the floristic regions 22. Altai and 23. Tarbagatai. The distribution of the species is limited by the Kalba, Southern Altai, Sarymsakty, Narym, Azutau, Ulba, Uba, Tarbagatai, Western Tarbagatai and Saur ridges. When studying the coenoflora of D. altaica, the completeness of the species composition of the communities was established. The coenoflora of D. altaica includes 175 species of higher vascular plants belonging to 127 genera and 42 families. The results obtained are necessary for monitoring and searching for historical habitats of D. altaica, compiling the route of field expedition trips, finding areas in natural habitats, and establishing phytocenotic relationships in D. altaica communities.
Keywords: East Kazakhstan; herbarium funds; inventory; floristic composition; Thymelaeaceae